Serum Fibroblast Growth Factor 23 Levels as a Predictor of Acute Kidney Injury in Critically Ill Obstetric Women in Obstetric Intensive Care Units: A North Indian Study - Munna Lal Patel; Shruti Gupta; Radhey Shyam; Rekha Sachan; Wahid Ali (Advanced Biomedical Research)
Background: Acute kidney injury (AKI) is associated with high mortality, over 30% in the majority of studies. The aim of this study was to evaluate the role of serum fibroblast growth factor 23 (FGF-23) inprediction of AKI in critically ill obstetric women. Materials and Methods: A prospective observational study was carried out in an intensive care unit (ICU) between September 2021 and August 2022. Critically ill obstetrics patients admitted in ICU between 18 and 40 years were included. Patients with ICU stay less than 24 hours, admissionfor low-risk conditions and airway monitoring, serum creatinine more than 4.5 mg/dl, or pre-existing renal disease were excluded. A total of 108 patients were recruited; seven were excluded; finally, 101 patients were enrolled for further analysis. 5ml venous blood was obtained; the first sample was obtained at the time of enrolment, and the secondsample was obtained after 48 hours of admission. Estimation of FGF-23 level was performed by using enzyme-linkedimmunosorbent assay. Disease severity was assessed by Acute Physiology and Chronic Health Evaluation IIscoring on the day of ICU admission. Results: A total of 650 obstetric cases were admitted in ICU during a period of 1 year, out of which 183 had AKI; the incidence of AKI was 28.1%. The most common risk factor associated with AKIin critically ill obstetric patients was hypertensive disorders of pregnancy (59.0%). On day 1, at a cutoff value of 296pg/ml, serum FGF-23 discriminates AKI from non-AKI with a sensitivity of 100%, a specificity of 90%, a positive predictive valueof 97.33%, a negative predictive valueof 100%, and an area under the curve of 0.949. Conclusion: Serum FGF-23 is a good marker for early prediction of AKI with 100% sensitivity and 90% specificity.